The relationship between isolated hypertension with brain volumes in UK Biobank - Newby, D; Winchester, L; Sproviero, W; Fernandes, M; Ghose, U; Lyall, D; Launer, LJ; Nevado-Holgado, AJ (Wiley, 2022)
Background Hypertension is a well-established risk factor for cognitive impairment, brain atrophy, and dementia. However, the relationship of other types of hypertensions, such as isolated hypertension on brain health and its comparison to systolic-diastolic hypertension (where systolic and diastolic measures are high), is still relatively unknown. Due to its increased prevalence, it is important to investigate the impact of isolated hypertension to help understand its potential impact on cognitive decline and future dementia risk. In this study, we compared a variety of global brain measures between participants with isolated hypertension to those with normal blood pressure (BP) or systolic-diastolic hypertension using the largest cohort of healthy individuals.